Submucosal lipoma of the stomach – a rare benign gastric tumour - Agarwal, RK; Regmi, R; Paudel, G; Pradhan, A; Agarwal, M; Agrawal, CS (Health Renaissance, 2012)
DOI: http://dx.doi.org/10.3126/hren.v10i1.6011 HREN 2012; 10(1): 62-63